Glaucous Gull Predation on Dovekies: Three New Hunting Methods - Jakubas, Dariusz; Wojczulanis-Jakubas, Katarzyna (ARCTIC, 2010)
We describe three previously unreported methods that hunting glaucous gulls (Larus hyperboreus) use to capture nesting and fledgling dovekies (Alle alle). During the nesting period, the pale-gray and white gulls camouflaged themselves by perching with head lowered on remnant snow patches in the dovekie colony, trying to ambush flying adults. We observed two other glaucous gull hunting methods on the open fjord water after the dovekie fledglings had left the colony. Gulls approached young dovekies in a fast, low-level glide, presumably to surprise the prey, and attempted to snatch them from the water. Gulls also swam rapidly towards young dovekies, zigzagging among small ice floes, presumably to confuse the birds and catch them before they could dive. The methods described, representing technical foraging innovations, supplement the evidence that gulls are a bird family that displays a diverse foraging innovation repertoire. Nous décrivons trois méthodes jamais signalées auparavant auxquelles recourent les goélands bourgmestres (Larus hyperboreus) pour capturer les mergules nains (Alle alle) aux stades de la nidification et de l’envol. Pendant la période de nidification, les goélands gris clair et blancs se camouflagent en se rabaissant la tête dans les restes de bancs de neige au sein des colonies de mergules nains afin d’essayer de piéger les adultes capables de voler. Nous avons observé deux autres méthodes de chasse de la part des goélands bourgmestres sur les eaux libres du fjord une fois que les mergules nains prêts à l’envol ont quitté la colonie. Les goélands s’approchaient des jeunes mergules nains en glissant rapidement et à faible altitude, vraisemblablement pour surprendre leurs proies, et essayaient de les arracher de l’eau. Les goélands se mettaient aussi à nager rapidement vers les jeunes mergules nains, en zigzaguant entre les bancs de glace flottante, probablement pour mélanger les oiseaux et pour les attraper avant qu’ils n’aient le temps de plonger. Les méthodes ainsi décrites, qui ...